ANALISIS REMUNERASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMPETENSI PEGAWAI BADAN PENGELOLAAN KEUANGAN, PENDAPATAN DAN ASET DAERAH KABUPATEN TUBAN - Stefanus Seto Susilo; Sundjoto, Sundjoto; Sri Rahayu (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to examine and explain the influence of remuneration, workload, and competence on employee performance, as well as to analyze the mediating role of competence in the relationship between remuneration and workload on employee performance at the Regional Financial, Revenue, and Asset Management Agency of Tuban Regency. The population in this study consists of all civil servants within the agency, totaling 100 individuals, with the sample determined using a saturated sampling (census) method. Data analysis was conducted using the Partial Least Squares (PLS) approach with the help of SmartPLS 3.0 software. The results show that remuneration has a positive influence on employee performance, workload also affects employee performance, and employee competence significantly impacts performance. Furthermore, competence is proven to mediate the effects of remuneration and workload on employee performance.